Coordinative threshold in race walking - Neumann, H. F.; Krug, J.; Gohlitz, D. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
According to the international competition rules race walkers have to keep contact to the ground and their knee straightened. In order to investigate the influence of adhering to the rules 20 race walkers performed a step test on a treadmill. Depending on velocity, movement coordination changed from a correct walking technique to an incorrect one and afterwards to running. Incorrect walking begins with occurrence of flight time and bending knee dependent on performance level between velocities of 2.75 to 4.0 m/s. The investigation shows a linear function between velocity and flight time, and a nonlinear one between velocity and knee straightening. To mark the maximum increase of offence against knee rule in course of velocity the term of coordinative threshold is introduced.